Proses Pembuatan Roda Gigi Helix Di Mastercam Untuk Mesin CNC 4-Axis VMC-550L - Jajang Nurhidayatulloh (LPPM Universitas Putera Batam, 2022)
Helical gears are a type of gear with a slanted tooth direction (not perpendicular to the face of the gear). The inclination or helix angle of the teeth on these gears is about 15-30 degrees. Computer-aided design & computer-aided manufacturing (CAD/CAM) software is used to design and manufacture prototypes, finished products, and product production processes. CAD/CAM applications are used to design products and program manufacturing processes, in particular, CNC machining. The purpose of this research is to discuss the process of making Helix Gears in Mastercam for 4-Axis Vmc-550L Cnc Machine, the implementation method starts from observation, problem formulation, library research, data collection, engineering drawings (CAD) design, CAM creation, simulation in applications, the final result of the helix gear the process takes 4 hours 9 minutes